THE RESILIENCE OF WOMEN TOURISM WORKERS DURING THE Covid-19 PANDEMIC IN BALI - Widiastini, Ni Made Ary; Rosa, Siti Annisa Silvia; Putera, Roni Ekha; Susilowati, Gabriella; Wibowo, Totok Hari (Universitas Padjadjaran, 2021)
This study aims to determine the form of resilience of women tourism workers affected by the Covid-19 pandemic. This study uses a qualitative method with a case study approach. Data sources are primary data from interviews with various parties, including hotel owners, hotel associations and hotel employees, while secondary data sources are documentation data. Data analysis was performed using an interactive model. The spread of the corona virus globally has affected various lines of community life, including in Bali. Hotels are the tourist facilities in Bali that are most affected. The decline in tourist visits, causing hotel occupancy rates to experience a drastic drop which resulted in layoffs. The finding of this research is that job termination for female employees occurs in almost every hotel in Bali. However, the termination of employment was responded creatively. In an effort to maintain a life for themselves and their families, women who are affected by hotel employees, especially those who have worked in the food and beverage division, react by adjusting to the conditions that occur. They make various types of food that are sold online using WhatsApp, I.G. and F.B. social media. The attitude of women who are former hotel workers in the food and beverage division in Bali towards termination of employment shows that creativity is driven by the spirit of survival as a modality that needs to be supported and worthy of being a good practice as well as a model on develop women’s capacities during pandemic Covid-19 and new normal.